Online Community College Student-Researchers Explore Mental Health Stigmas: Deeper Learning Implied. Issue 4 (2nd April 2020) - Lovell, Elyse D'nn; Corder, Celeste; Rainville, Anna; Ramus, Mcken-Z; Hart, Zachary; McElroy, Cherish; Robinson, Hayli; Robinson, Amanda
ABSTRACT: The purpose of this study was to assess learning through the integration of student-research within a community college online Abnormal Psychology course, contained in a one-semester behavioral health certificate program. Seven abnormal psychology students became researchers with IRB approval, and they conducted a qualitative study about mental health stigmas interviewing participants ( N = 14). The students varied – first college experience to a senior attending a four-year institution and each located hundreds of miles apart in rural Rocky Mountain communities. To develop themes, student-researchers shared literature and participants' quotes within online discussion boards using a hermeneutic design. Findings clarified that mental health stigmas differed when considering participants' ages, education, and family history. Among student-researchers, deeper learning was evidenced as a majority of students described a most important part of their learning as their research experience, and they applied their learning about mental health stigmas to their personal lives and career aspirations.